PENGARUH PENGELOLAAN ARSIP TERHADAP EFISIENSI KERJA DI SUB BAGIAN KEPEGAWAIANRSUD DR. SOEDIRMAN KEBUMEN - Khasanah, Uswatun; ., Sutriono (ANALISIS FAKTOR-FAKTOR PENYEBAB TERJADINYA KREDIT MACET PADA KUD RAHMAT WIDODO KECAMATAN SRUWENG KABUPATEN KEBUMEN, 2018)
Archives are documents (original text) that are made and received by States Institution and Government/Private/Individual Departrment in various forms, both single and collective for government activity and nation life. The purpose of the researh is to know how the effect of management of the archives of work efficiency in Sub-section of staffing RSUD Dr. Soedirman Kebumen. The problems which are studied including: (1) how the management of archives in Sub-section of staffing RSUD Dr. Soedirman Kebumen, (2) the effect of management archives of work efficiency in Sub-section of staffing RSUDDr. Soedirman Kebumen. This research was conducted at the RSUD Dr. Soedirman Kebumen located in the Lingkar Selatan Muktisari street Kebumen by taking the subject of research, officials or employees in the sub-section of staffing. This type of research is descriptive method and regression and correlation method. While data collection method used is monitoring (observation), interviews,  and questionnaires. From the results of this research, it is known that there is strong positive relationship between the management of the archive of work efficiency in sub-section of staffing  RSUD Dr. Soedirman Kebumen . It is evident from the pearson correlation test results earned value 0,910 and calculation of questionnaires that States 82,8% work efficiency in sub-section of staffing RSUD Dr. Soedirman Kebumen influence by management of archive while 17,2 % influence by another factor. The problem of management of the archive is limitedness of officer to handle the archive. Thus, the need for special officer in managing the archive.